If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4r + -8 + -3r + 3 = 2r + 12 Reorder the terms: -8 + 3 + 4r + -3r = 2r + 12 Combine like terms: -8 + 3 = -5 -5 + 4r + -3r = 2r + 12 Combine like terms: 4r + -3r = 1r -5 + 1r = 2r + 12 Reorder the terms: -5 + 1r = 12 + 2r Solving -5 + 1r = 12 + 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. -5 + 1r + -2r = 12 + 2r + -2r Combine like terms: 1r + -2r = -1r -5 + -1r = 12 + 2r + -2r Combine like terms: 2r + -2r = 0 -5 + -1r = 12 + 0 -5 + -1r = 12 Add '5' to each side of the equation. -5 + 5 + -1r = 12 + 5 Combine like terms: -5 + 5 = 0 0 + -1r = 12 + 5 -1r = 12 + 5 Combine like terms: 12 + 5 = 17 -1r = 17 Divide each side by '-1'. r = -17 Simplifying r = -17
| 5x-2(2x+14)=12 | | Z+1(2z+3)=15 | | 5t^2-55t+90= | | -5/8x-2-5 | | 5x-2(-2x+14)=12 | | 33b=c/t | | z-4z=9z-5-z | | s^2-7s+12= | | 2x+15=X^2+12x+36 | | .2x-.08(x-10)=24.80 | | 1/5-1/2p=5/8 | | y-121=0 | | 4/x+1/2x= | | 56x^2=0 | | (x+1/4)+5=(x+6/7) | | (85+2m)15=36 | | 16y-4=20y+32 | | -8(n+4)=-7n-36 | | (x/2)+(4/9)=(x/9)-(4/9) | | x^2/3-9x^1/3-6=0 | | 3x+2+2x+4= | | 12-3*0= | | s^2+5s+4= | | 8x-1=6+7x | | 5n+11=66 | | 8x-1=6+7 | | 2(x+9)+4x=54 | | x/-12=12 | | .1(x+80)+0.2x=14 | | |-10|-12+1= | | w-45=45 | | 2*x^3-5*x^2+7*x-4=0 |